Towards a new approach for coastal governance with an assessment of the Plettenberg Bay nearshore linefisheries - Smith, Martin Kyle Stratford (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2006)
Under the guidance of the new coastal management policies within South Africa this thesis advocates a more integrated, co-operative approach to local coastal management. The project aimed to acquire baseline information on the local nearshore fishery and resource state and to propose a set of indicators that could be incorporated into the new management strategy. To gather the required information the project was split into two parts: 1) An assessment of the local linefisheries and 2) A comparative study of the reef fish community structure between exploited and unexploited reefs. The local linefisheries were assessed through the use of launch records, commercial catch records, access point and boat based surveys. A questionnaire was used to gather data on catch and effort, fisher demographics, fisher attitudes towards and knowledge of the current management regulations, assess the efficacy of the fisheries inspectorate and highlight spatial areas of fishing pressure. A total of 252 interviews and catch inspections were conducted. Total effort for the ski-boat fishery estimated from the access point survey was 890 boat days.yearâ »Â¹ or 3560 fisher days. yearâ »Â¹ compared to 736 boat days.yearâ »Â¹ or 2944 fisher days. yearâ »Â¹ recorded in the launch records. Effort was seasonal with greater pressure occurring over the summer holiday period. Analysis of the catch showed that Merluccius capensis, Argyrozona argyrozona, Argyrosomus inodorus, Chrysoblephus laticeps and Atractoscion aequidens were the most frequently caught species. The overall CPUE was 3.00Â±5.54kg.fisherâ »Â¹.dayâ »Â¹ or 4.71Â±4.117 fish.fisherâ »Â¹.dayâ »Â¹. Estimated targeted CPUE was 0.91Â±0.67kg.fisherâ »Â¹.dayâ »Â¹ or 0.97Â±0.77 fish.fisherâ »Â¹.dayâ »Â¹ for C. laticeps, 8.47Â±8.57kg.fisherâ »Â¹.dayâ »Â¹ or 1.24Â±1.16 fish.fisherâ »Â¹.dayâ »Â¹ for A. aequidens and 2.05Â±3.78kg.fisherâ »Â¹.dayâ »Â¹ or 1.10Â±1.80 fish.fisherâ »Â¹.dayâ »Â¹ for A. inodorus. Issues identified included poor fisher knowledge regarding linefish regulations, the low occurrence of fishery inspections and a limited degree of noncompliance. Although most fishers supported the current linefish management regulations, when tested on the size limits, bag limits and closed seasons of their target species a high proportion of fishers did not know the regulations (recreational 64%, charter 53%, commercial 42%). Furthermore only 27% of fishers had had their catch inspected whilst fishing in Plettenberg Bay and the majority of these had only been inspected once. Just over half the interviewees (60%) indicated that fishing had deteriorated within Plettenberg Bay with fewer and smaller fish being caught. The most common causes cited for this decline were commercial and recreational overfishing respectively. Underwater point counts and experimental angling were used to rapidly assess the state of the reef fish resource in Plettenberg Bay through a comparative study of the community structure between two exploited sites in Plettenberg Bay and two protected sites within the Tsitsikamma National Park. Generalized linear modeling showed that relative density of certain species was significantly different between the protected reefs inside the TNP and those exploited reefs within Plettenberg Bay. Both P. rupestris and C. laticeps had greater densities within the protected area whilst Chisquared tests showed that the size frequency distributions were significantly different with larger size-classes and the maximum size of fish greater within the reserve. These trends were noted with both the underwater visual surveys and the experimental angling. Multi-dimensional scaling and cluster analysis showed that there was an overall difference in the community structure between the study sites. It is hypothesised that through removal of key reef species and larger individuals that fishing has directly and indirectly affected the overall community structure. Within a simple framework based on ecological, institutional and social sustainability domains along with the results of the study area, a set of indicators is proposed and the sustainability of the local fishery scored within a rapid assessment matrix. The socio-economic domain scored the highest (83%) whilst the institutional domain scored the lowest (8.3%) and the ecological domain scored 25%, giving a total sustainability score of 38.8%. The results of this matrix show that at present the local fishery is non-sustainable and in need of greater management. By synthesizing papers dealing with and based on the concepts involved in Integrated Coastal Management, a structured approach is proposed to developing and implementing more holistic local coastal governance. It is envisaged that the framework to implement such an approach should be through the development of a local Coastal Management Plan and a subsidiary Bay Management Plan. Although stakeholder participation and representation is an essential component in the development of these plans, it is recommended that the local municipality should be the lead agent and incorporate the plans into the local Integrated Development and Spatial Plans thereby gaining long term local government support.
Keywords: Fishery management -- South Africa -- Plettenberg Bay; Fisheries -- South Africa -- Plettenberg Bay; Reef fishes -- South Africa -- Plettenberg Bay; Coastal zone management -- South Africa -- Plettenberg Bay